2018
DOI: 10.1002/ange.201810891
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Induced Self‐Assembly of Cooperative Catalysts

Abstract: Dissipative self-assembly processes in nature rely on chemical fuels that activate proteins for assembly through the formation of an oncovalent complex. The catalytic activity of the assemblies causes fuel degradation, resulting in the formation of an assembly in ahigh-energy,out-of-equilibrium state.H erein, we apply this concept to as ynthetic system and demonstrate that as ubstrate can induce the formation of vesicular assemblies,w hich act as cooperative catalysts for cleavage of the same substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In the past, the close proximity of TACN⋅ Zn 2+ groups needed for catalysis have been achieved by their direct covalent attachment to dendrimers or immobilization onto nanoparticles . Recently, we demonstrated that cooperativity between TACN⋅ Zn 2+ groups can also be achieved within substrate‐induced vesicular assemblies . Marked differences in catalytic activity were observed between the non‐assembled state (at concentrations below the critical assembling concentration; CAC) and the assembled state (above the CAC).…”
Section: Figurementioning
confidence: 99%
“…In the past, the close proximity of TACN⋅ Zn 2+ groups needed for catalysis have been achieved by their direct covalent attachment to dendrimers or immobilization onto nanoparticles . Recently, we demonstrated that cooperativity between TACN⋅ Zn 2+ groups can also be achieved within substrate‐induced vesicular assemblies . Marked differences in catalytic activity were observed between the non‐assembled state (at concentrations below the critical assembling concentration; CAC) and the assembled state (above the CAC).…”
Section: Figurementioning
confidence: 99%
“…52 Therefore, due to their ability to provide a hydrophobic environment, nanoscopic scale, chemical promiscuity, diffusional interactions, and polarity gradients, micelles have been widely exploited as models for microcompartments. In this regard, a number of dynamic systems presenting complex behavior have been reported: dissipative fueled self-assemblies of nanoreactors 53,54 with catalytic activities, 55,56 micelles based on the reversible self-assembly of imine-based surfactants, 57 amphiphilic imines 58 displaying self-replication 59 and autopoietic properties 60 as well as out-of-equilibrium self-replicating micelles, 61 able to generate autonomously supramolecular oscillations. 62 Autocatalysis and self-replication are essential for the organization and outcomes of both artificial 63−66 and biological 67,68 reaction networks.…”
Section: Introductionmentioning
confidence: 99%
“…A common approach for constructing new chemical reaction cycles is to combine multiple reactions (Figure 1A, Left). The individual reactions can be either catalytic [25][26][27][28][29][30][31][32][33][34] or non-catalytic, [35][36][37][38][39][40][41][42][43] and can incorporate enzymatic reactions. [44][45][46][47][48][49] With biomolecules such as nucleic acids and enzymes, high specificity can be achieved and multiple reactions proceed concurrently under the same conditions.…”
Section: Introductionmentioning
confidence: 99%